The art of creating futures - practical theology and a strategic research sensitivity for the future - J. A. van den Berg; R. R. Ganzevoort (Acta Theologica)
This paper explores a futures perspective for practical theology. Although there are some examples of a future orientation, a systematic futures perspective has not been developed. Building on futures studies (including predictive studies on foresight and design and architecture studies), the authors propose a methodological model for future-sensitive practical theology, accounting for the probable, possible, and preferable. The model results in three modes in which practical theology can employ a future orientation: utopian, prognostic-adaptive, and designing-creative.